A study on the optimal arrangement of tube bundle for the performance enhancement of a steam turbine surface condenser. (5th February 2020) - Park, Yong Gap; Yoon, Sang Youl; Seo, Young Min; Ha, Man Yeong; Park, Young Min; Koo, Byoung Soo
Highlights: A condensation model was developed to predict the condenser performance. The condenser performance was analyzed using various numerical results. Detailed effects of the various parameters of tube bundle were discussed. The numerical results were verified with the experiments. The optimized model had a better pressure drop performance than the base model. Abstract: A porous medium model was used for numerical and experimental investigations of a system that includes a tube bundle inside a steam turbine surface condenser. A condensation model was developed to predict the condenser performance using user-defined functions (UDFs) in the commercial computational fluid dynamics software FLUENT. The shell-side pressure drop around the tube bundle is an important indicator for the condenser performance and can be used to compare different condenser-tube arrangements. The condenser performance was analyzed using various numerical results, such as the absolute pressure, condensation mass flow rate, velocity magnitude, and air mass fraction. Detailed effects of the various parameters of tube bundle are discussed. These parameters had a great influence on the condenser performance. The numerical data were generally in good agreement with those obtained by experiments. An important practical finding from this study is that changing tube bundle can significantly improve the condenser performance by reducing the shell-side pressure drop. Consequently, the optimized model has approximately 40% better pressure drop performance than the base model, and the numerical results were verified with the experiments established by Donghwa Entec.